Endoscopic radial incision and cutting for benign stenosis of the lower gastrointestinal tract: An investigation of novel endoscopic treatment in multicenter trial. Issue 8 (11th May 2022) - Moroi, Rintaro; Shiga, Hisashi; Nochioka, Kotaro; Chiba, Hirofumi; Shimoyama, Yusuke; Kuroha, Masatake; Tosa, Masaki; Kakuta, Yoichi; Kayaba, Shoichi; Takahashi, Seiichi; Kinouchi, Yoshitaka; Masamune, Atsushi
Abstract: Background and Aim: The standard therapies for benign gastrointestinal stenosis are endoscopic balloon dilation or surgery; each have their advantages and disadvantages. In contrast, radial incision and cutting (RIC) is a novel approach for such stenosis. This study aimed to investigate the feasibility, safety, and effectiveness of RIC. Methods: We enrolled 20 patients with benign stenosis of the lower gastrointestinal tract developed by various causes and conducted RIC. We evaluated the re‐intervention free rate 52 weeks after RIC, technical success rate, adverse events, procedure time, and improvement of symptoms using a visual analog scale. Results: We performed 20 sessions of first RIC for 20 lesions and seven sessions of additional RIC due to re‐stenosis. The cumulative re‐intervention‐free survival rate 52 weeks after the first RIC was 55.8%. The technical success rate of the first RIC was 100% (20/20) while that of the additional RIC was 85.7% (6/7). One case developed perforation during the additional RIC and urgent surgery was performed. The additional RIC tended to show worse results in adverse events and procedure time compared with the first RIC. The patients' symptoms including abdominal bloating and dyschezia were significantly improved. Conclusions: Although RIC demonstrated a higher technical success rate for lower gastrointestinal stricture and subsequent improvement of patient symptoms, several issues including preventing delayed bleeding, perforation, and the long‐term prognosis should be solved and clarified in further investigations.